2020
DOI: 10.1049/hve.2019.0257
|View full text |Cite
|
Sign up to set email alerts
|

Review on development of carbon nanotube field emission cathode for space propulsion systems

Abstract: In recent years, small‐size, low‐weight aerospace propulsion systems have developed rapidly for space exploration, on‐orbit scientific instruments and extra space missions, while additional electron emission devices are commonly required in those propulsion systems. Carbon nanotube (CNT) based field emission cathodes exhibit extraordinary field emission properties and are regarded to be an ideal alternative of conventional thermionic or hollow cathodes. In this study, the authors give an overview of present st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
(59 reference statements)
0
17
0
1
Order By: Relevance
“…Taking into account the discussion above, the electron field emission [18,19] and Hump theory [20], and our previously obtained results [8], a simplified circuit diagram of the charged As shown in Figure 11, it was concluded that the operation mechanism of the AC d -µCAT was as follows [8]. First, when a high voltage was applied on the μCAT, a strong electric field E c formed on its cathode surface.…”
Section: Operation Mechanism Of the Ac D -µCatmentioning
confidence: 73%
See 1 more Smart Citation
“…Taking into account the discussion above, the electron field emission [18,19] and Hump theory [20], and our previously obtained results [8], a simplified circuit diagram of the charged As shown in Figure 11, it was concluded that the operation mechanism of the AC d -µCAT was as follows [8]. First, when a high voltage was applied on the μCAT, a strong electric field E c formed on its cathode surface.…”
Section: Operation Mechanism Of the Ac D -µCatmentioning
confidence: 73%
“…Taking into account the discussion above, the electron field emission [18, 19] and Hump theory [20], and our previously obtained results [8], a simplified circuit diagram of the charged particles, mainly including the ion and electron flow for the AC d ‐µCAT operation, is proposed and presented in Figure 11.…”
Section: Operation Mechanism Of the Acd‐µcatmentioning
confidence: 99%
“…( 2) and ( 3)) decreases. Field emission-type electron sources, such as carbon nanotube cathodes, 3) have also been investigated. Such electron sources do not require a working gas; however, their emission current density is limited 4) (i.e., on the order of 1 A/m 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Field emitters, owing to their unprecedented advantages over the conventional thermionic emitters (hot cathodes), have been realized as potential candidates in various vacuum microelectronic devices, and for space applications, in particular for electric propulsion systems and amplifiers. [1][2][3][4][5] Over the past decades, many FE-based electric propulsion (FEEP) thrusters have been developed and deployed for space missions. [6,7] Moreover, the field emitters also work as an efficient neutralizer in ion thrusters, and electrodynamic tethering.…”
Section: Introductionmentioning
confidence: 99%